2005
DOI: 10.4049/jimmunol.174.12.7716
|View full text |Cite
|
Sign up to set email alerts
|

IgE Generation and Mast Cell Effector Function in Mice Deficient in IL-4 and IL-13

Abstract: IL-4 and IL-13 are potent cytokines that drive production of IgE, which is critical to the development of atopic disease. In this study, we directly compared IgE generation and IgE-dependent mast cell effector function in mouse strains lacking IL-4, IL-13, IL-4 + IL-13, or their common receptor component, IL-4Rα. Although serum IgE was undetectable under resting conditions in most animals deficient in one or both cytokines, peritoneal mast cells from mice lacking IL-4 or IL-13 had only partial reductions in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 64 publications
(52 reference statements)
3
55
0
3
Order By: Relevance
“…Of these, IL-4 especially induces isotype switching in B cells, from IgG to IgE production, regulation of the chemokines required for eosinophil migration, and might increase mucus secretion in allergic airways [32][33][34]. In this study, treatment with CJE attenuated the increase in IgE (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Of these, IL-4 especially induces isotype switching in B cells, from IgG to IgE production, regulation of the chemokines required for eosinophil migration, and might increase mucus secretion in allergic airways [32][33][34]. In this study, treatment with CJE attenuated the increase in IgE (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…IL-4 up regulates the expression of endothelial vascular cell adhesion molecule-1 (VCAM-1) which interacts with very late antigen-4 (VLA-4) and promotes the recruitment of eosinophils [27]. IL-4 also causes class switching in B cells to synthesize IgE which involves in mast cell degranulation by cross linking with IgE receptors [28]. Here, we demonstrated that mepacrine reduced IL-4 as well as OVA-specific IgE levels.…”
Section: Discussionmentioning
confidence: 84%
“…IL-4 causes B cells to synthesize IgE, which is involved in mast cell degranulation by cross-linking IgE receptors [27]. IL-5 enables the terminal differentiation and proliferation of eosinophil precursors and the eosinophil activation effect [28].…”
Section: Discussionmentioning
confidence: 99%